Common Ear, Nose & Throat Problems in the Under- Five Sudanese Children - Osman, Wail N; Elmustafa, Osman M; Abd Elgalil, Inas Mohamed (مجلة الجزيرة للعلوم الصحية; مجلد 9 عدد 1 (2013), 2013)
Introduction: The health problems of children and especially the under-5 years are of great concern and impact on both medical and surgical practice. No wonder they attract political and administrative concern Objective : This study aims to identify the common Ear, Nose & Throat (ENT) problems of under-5 Sudanese children and to study the frequency, admissions, available beds and operations and to compare this work load with the rest of the ENT wards. Furthermore, to outline what is needed to improve the services for this age group. Methodology : This is a retrospective hospital–based study including all patients (n=21384) who presented to the ENT department, Wad-Medani Hospital, Gezira, Sudan, during a period of two years from the first of January 2010 to the thirty first of December 2011. Results : The total number of the under-5 children was 2330; which contributed to 41.32% of total paediatric age group, up to 16 years, (n=5639) and 10.90% of the total number of ENT patients who presented to the ENT department at Wad-Medani Hospital. The total number of admissions of under-5 children accounted for 32.72% of all paediatric patients and 20.66% of all ENT patients. Their commonest problems found in this study were; adenoiditis & tonsillitis (37.68%), otitis media (27.25%), Upper respiratory tract infections (URTIs) & allergy (12.31%), foreign body related (12.23%), otitis externa (5.45%), others (3.43%), epistaxis (0.75%), hearing & speech disorders (0.90%). The total number of children under-5 requiring surgical operations constituted 55.46% of all paediatric patients and 33.98% of the total number of all ENT patients who were operated on. Of these operations 57.01% were elective and 42.99% were emergency operations. The main indications in 94.77% of the elective operations were adenoidectomy & tonsillectomy, while most of the surgical emergencies 91.32% were due to foreign body related problems. Conclusions : The ENT problems of the under-5 children in Wad-Medani General Hospital constitute an obvious high proportion of the work load. More attention is to be paid to this age group in terms of facilities, staff training and special requirements needed in settings and equipments. Thus, better handling and outcomes could be achieved for this important and delicate age group.